Effect of dipeptidyl peptidase-4 inhibitors on fat metabolism in patients with type 2 diabetes mellitus - A S Ametov; D G Gusenbekova (Терапевтический архив, 2014)
AIM. To evaluate the effect of sitagliptin in combination with metformin on glucose toxicity and lipotoxicity in patients with type 2 diabetes mellitus. MATERIALS AND METHODS. Eighty-two overweight and dyslipidemic patients (mean age 55.3±9.1 years) who had not achieved the goal levels of glycated hemoglobin (HbA1c) (mean level 8.3±1.6%) during metformin therapy and dietotherapy were examined. Group 1 patients received sitagliptin 100 mg/day in combination with metformin 2 g/day; Group 2 took metformin 1.5-2 g/day. The levels of fasting plasma glucose (FPG) levels, postprandial glycemia (PPG), HbA1c, body weight, body mass index, waist circumference, and waist-to-hip ratio, blood lipid composition, and the levels of insulin, leptin, adiponectin, HOMA-IR, and HOMA-Β were estimated at baseline and 6 months later. Visceral fat (VF) magnetic resonance imaging (MRI) was carried out. RESULTS. Following 6 months, both groups showed positive changes in FPG, PPG, and HbA1c levels. HbA1c decreased from 8.3±1.6 to 6.6±1.24% in Group 1 and from 8.35±1.75 to 7.62±1.39% in Group 2. PPG and FPG reduced by an average of 2.67 and 3.3 mmol/l in Group 1 and by 2.1 and 1.8 mmol/l in Group 2. HOMA-Β increased by 23.4. conventional units (CU) in Group 1 and by 4.8 CU in Group 2. HOMA-IR was noted to display positive changes in both groups. The level of adiponectin rose by 1.9 ng/ml in Group 1 and by 0.49% ng/ml in Group 2 and that of leptin fell by 7.37 and 1.21 ng/ml, respectively. There were significant differences between the groups in anthropometric changes. MRI revealed a significant VF drop by 20.6±13.5 cm2 (7.5%) in Group 1 and by 5.7±3.75 см2 (1.76%) in Group 2. CONCLUSION. Combined therapy with sitagliptin and metformin caused reductions in glucose toxicity and lipotoxicity.